Regulation of gene expression and RNA editing in Drosophila adapting to divergent microclimates - Arielle L. Yablonovitch (Nature Portfolio, 2017)
Environmental adaptation is generally studied at the genomic level, but it may also be driven by transcriptional processes. Here, the authors investigate variation in gene expression and RNA editing across diverging populations of Drosophila melanogaster from two microclimates.